Control of sorghum downy mildew of maize and sorghum in Africa - Bock, C.H.; Jeger, M.J.; Cardwell, K.F.; Mughogho, L.K.; Sherington, J. (2000)
In Africa, sorghum downy mildew (SDM), caused by Peronosclerospora sorghi, infects both sorghum and maize. Systemic infection can result in severe yield loss. The effects of seed treatments and foliar sprays of metalaxyl on the disease were determined on maize in Nigeria (1992) and sorghum in Zimbabwe (1993/4). Seed treatment at 1.0 g a.i/kg or a foliar spray at 0.96 g a.i./l significantly reduced the incidence of the disease, although the latter was less consistent. The effect on yield was less clear. In Nigeria, severe stem borer damage in some plots prevented definitive yield assessment in response to fungicide. In Zimbabwe, there was no effect of fungicide on sorghum yield due to the overriding influence of insect damage (1993) and drought (1994). Planting density of sorghum in Zimbabwe did not appear to influence disease incidence at the densities used. Metalaxyl can be used to control SDM effectively on sorghum and maize in Africa.